Exploring the Structure of Sibling Relationships Among Preschool Children in China and Developing a Questionnaire - Jiang, Meiru; Cao, Xiaojun; Huang, Qinqin; Wu, Siqi; Chen, Xu (Frontiers in Psychology, 2022)
Objective: To examine the structure of sibling relationship among preschool children in China and develop a questionnaire.Methods: The concept of sibling relationship among preschool children in China was established through literature review, open interviews, and expert review, and the initial project was designed. Using the questionnaire survey method, with 30 parents of preschool children and 621 preschool children as the research objects, we performed item analysis, exploratory factor analysis, confirmatory factor analysis, and reliability and validity test on the initial questionnaire.Results: The questionnaire for sibling relationship among preschool children in China had 18 questions in dimensions of sibling interaction, sibling acceptance, sibling warming, and sibling rivalry. The questionnaire fitting indexes were better (2/df = 1.829, CFI = 0.930, TLI = 0.917, RMSEA = 0.055, SRMR = 0.053). The internal consistency coefficient between the total questionnaire and each dimension was 0.759–0.8548, and the total questionnaire significantly correlated with each dimension (r = 0.229–0.792) and the total score of parental self-efficacy (r = –0.106 to 0.338).Conclusions: The questionnaire for sibling relationship among preschool children in China exhibited good reliability and validity, making it an effective tool for the evaluation of sibling relationship among preschool children.